GRP-073 Failure Mode and Effect Analysis in Improving the Safety of the Chemotherapy Process. (12th March 2013) - Hernandez, B; Bravo, C; Esteban, MJ; García, E; Candel, B; García, M; Castellanos, Y; Letellez, J; Sierra, J; Farfán, FJ
Abstract : Background: Medication errors in chemotherapy have a high potential to cause harm. Errors may occur during different steps of the medication process. Failure Mode and Effect Analysis (FMEA) is a proactive risk assessment method that enables potential risks to be identified and prioritises actions to improve safety. Purpose: To apply FMEA methodology to the chemotherapy process: prescribing, pharmaceutical validation, compounding and dispensing. Materials and Methods: Prospective study, in a tertiary level hospital, using the FMEA technique developed by the Veterans Affairs Healthcare System for the chemotherapy process. An interdisciplinary working group was created and meetings held over three months. Processes and subprocesses were described; potential failure modes and possible causes were identified. Main sources used were brainstorming and cause-effect-diagramming. For each failure mode, a Hazard Score (HS) was calculated by multiplying the probability of occurrence (Remote = 1, Uncommon = 2, Occasional = 3, Frequent = 4) and severity of effect (Minor = 1, Moderate = 2, Major = 3, Catastrophic = 4).If HS>=8, corrective actions were proposed. If HS < 8, failure mode was evaluated based on: lack of detection, criticality and absence of effective control measures. All data were collected in a validated worksheet. Results: A flow diagram was obtained. Twenty-seven failure modes were identified, and twenty had a HS>=8. Failure modes with the highest HS were: wrong dose calculation and wrong protocol (Prescribing); incorrect production protocol in the computer system and non-detection of wrong dose calculation (Pharmaceutical validation); wrong medicine is chosen, incorrect volume of drug added to diluent and labelling error (Compounding); Delivered to wrong nursing unit or patient (Dispensing). Corrective actions proposed were: policy of weighing patient for proper dose calculation, chemotherapy database updated, double checking, gravimetric control on prepared chemotherapy, procedures for proper patient identification (barcode identification system or radiofrequency dispensing system). Conclusions: FMEA contributes to the development of a very clear and shared vision of the chemotherapy process, taking into account different perspectives: oncologist, pharmacist, technician and nurse. FMEA is a useful tool for identifying critical parts of the chemotherapy process, prioritising corrective actions, minimising potential risks and improving the quality and safety of patient care. No conflict of interest.